KAJIAN NILAI BUDAYA KANDANG ADAT, DI SUMATERA SELATAN, SUKU KOMERING, SEBAGAI BENTUK IMPLENTASI KEARIFAN LOKAL BUDAYA NASIONAL - Sri Wahyuningsih; Sundari Sundari; Sri Husnulwati (JURNAL EDUCATION AND DEVELOPMENT, 2024)
This article discusses the cultural values ​​contained in the marriage customs of the Komering tribe of South Sumatra, as an effort to preserve South Sumatra's local culture. which aims to discover the cultural values ​​contained in the cultural values ​​of the marriage customs of the Komering tribe community as a form of local wisdom of the Komering tribe community, Ogan Komering Ulu. Regency. Qualitative descriptive methods were used in this research to examine and understand the cultural values ​​of the marriage customs of the people of South Sumatra, especially the Komering tribe, in this case the traditional Corral Culture custom before the marriage contract procession. Data was obtained using observation, interviews, documentation and literature study techniques. The data were analyzed using data processing techniques resulting from data collection in the field by direct observation of the community at the wedding procession of the Palembang community, specifically for the Komering tribe, at the data analysis stage through a qualitative approach, where the data collected is not in the form of numbers but rather by collecting data using interview and observation guidelines The results of the research are the lack of implementation of this traditional cage culture among the people of South Sumatra, so there is a need to study this traditional cage culture through efforts to provide outreach to the community, related parties, in this case the traditional cultural figures, the education sector. arts and culture, through direct promotion, verbal promotion (word of mouth) Leaflets, posters, newspapers.